LinguaBridge – academic digital scaffold - Gnanasagaran, Puvana; Jamaludin, Syaliana (2025)
LinguaBridge is an innovative AI-enabled digital platform designed to enhance academic literacy among TESL (Teaching English as a Second Language) students. Integrating advanced natural language processing (NLP), adaptive learning algorithms, and collaborative tools, LinguaBridge effectively addresses the challenges TESL students face when navigating complex academic texts. Its key features include NLP-driven text simplification, contextual cues, dynamic glossaries, multimodal learning supports (videos, podcasts), spaced repetition quizzes, and real-time analytics. Preliminary pilot studies demonstrate that learners using LinguaBridge significantly improved reading comprehension scores (an average increase of 15%) and vocabulary retention (up to 20 percentage points higher) compared to traditional study methods. Remarkably, study time was reduced by 30–50%, enhancing learning efficiency. Furthermore, LinguaBridge promotes global teaching readiness by offering region-specific teaching examples and recommending targeted, high-impact ELT resources. The platform uniquely employs a hybrid AI-human scaffold approach, combining cognitive, social, and pedagogical support, fostering deeper comprehension and engagement. Overall, LinguaBridge represents a transformative approach to TESL teacher education, effectively bridging the gap between theory, practice, and cultural adaptability.